A Model of the Argon Oxygen Decarburization Process for Refining Stainless Steel - A. C. Burrow; R. P. King (Society for Mining, Metallurgy & Exploration, 1990)
A dynamic model that predicts the variation of carbon content with time in the argon-oxygen decarburization (AOD) process has been developed. The model recognizes three distinct zones in the AOD vessel: the tuyere region in which the blown oxygen reacts very rapidly with the metal components in the molten alloy; a region in which bubbles of inert gas and oxide drop lets rise through the molten alloy; and a zone in which the slag layer can interact with the molten alloy. The process is dynamically controlled by the rate at which dissolved oxygen, produced on the surface of rising oxide droplets, and dissolved carbon diffuse through the molten alloy to react at the surface of the rising bubbles. The rate at which carbon and oxygen react on the bubble surface is assumed to be intrinsically very fast. Predicted decarburization rates compare reasonably well with rates measured in the AOD vessel at Middleburg Steel and Alloys. The model has been developed primarily to allow development of a time-optimal blowing stategy for the AOD vessel.